Non-invasive prenatal testing reveals copy number variations related to pregnancy complications - Guangping Wu (Molecular Cytogenetics, 2019)
Abstract Background Pregnancy complications could lead to maternal and fetal morbidity and mortality. Early diagnosing and managing complications have been associated with good outcomes. The placenta was an important organ for development of pregnancy complications. Thus, non-invasive prenatal testing technologies could detect genetic variations, such as aneuploidies and sub-chromosomal copy number variations, reflecting defective placenta by maternal plasma cffDNAs. Maternal cffDNAs had been proved to derive from trophoblast cells of placenta. Results In order to find out the relationship between genetic variations and pregnancy complications, we reviewed NIPT results for subchromosomal copy number variations in a cohort of 3890 pregnancies without complications and 441 pregnancies with pregnancy complications including gestational diabetes mellitus (GDM), pregnancy-induced hypertension (PIH), preterm prelabor rupture of membranes (PPROM) and placenta implantation abnormalities (PIA). For GDMs, we identified three CNV regions containing some members of alpha- and beta-defensins, such as DEFA1, DEFA3, DEFB1. For PIHs, we found three duplication and one deletion region including Pcdhα, Pcdhβ, and Pcdhγ, known as protocadherins, which were complicated by hypertensive disorders. For PPROMs and PIAs, we identified one and two CNV regions, respectively. SFTPA2, SFTPD and SFTPA1, belonging to surfactant protein, was considered to moderated the inflammatory activation within the fetal extra-embryonic compartment, associated to duration of preterm prelabor rupture of fetal membranes, while MEF2C and TM6SF1 could be involved in trophoblast invasion and differentiation. Conclusions Our findings gave a clue to correlation between genetic variations of maternal cell-free DNAs and pregnancy complications.